(untitled) (SCIENCE TIME JOURNAL, 2026)
In the article semantic fields and associative networks in the works of Edward Young from a psycholinguistic perspective are aimed to analyse. Focusing primarily on Night Thoughts, the study analyzes how emotionally marked lexical units, metaphorical oppositions, and existential concepts form interconnected semantic structures that activate readers’ cognitive and emotional processes. The findings demonstrate that Young’s poetic language functions as a psychological mechanism shaping inner speech, existential reflection, and affective responses, thereby confirming the relevance of his work for contemporary psycholinguistic research.